Lachnoclostridium-mediated fermentation of Konjac glucomannan: short chain fatty acids production and inhibitory xanthine oxidase activity - Deng, Jie; Liang, Yuxuan; Zhang, Zhiming; Yang, Zhiyi; Bao, Yilu; Nong, Yanyan; Wang, Hongmei; Zhao, Chenhui; Mai, Shenghong; Tan, Cong; Pan, Yingxue; Feng, Caimin; et al. (Frontiers in Nutrition, 2025)
Hyperuricemia (HUA) is notably prevalent in various regions. In China, it has become the second most prevalent metabolic disorder. Since the adverse effects of conventional uric acid-lowering drugs, there is an urgent need to develop natural and safe therapeutic alternatives. Previous studies have shown that Konjac glucomannan (KGM) can effectively reduce serum uric acid levels in HUA rats and modulate gut microbiota composition, particularly by increasing the abundance of Lachnoclostridium. To further elucidate the underlying mechanisms, this study investigated the fermentation characteristics of KGM by Lachnoclostridium and its inhibitory effects on xanthine oxidase (XOD) activity. The results revealed that KGM fermentation with Lachnoclostridium reduced the pH and significantly lowered the apparent viscosity. Reducing sugar content decreased while short chain fatty acids (SCFAs) increased significantly. Furthermore, prolonged fermentation enhanced the XOD inhibitory activity of KGM. These findings suggested that KGM may exert its uric acid-lowering effects by promoting Lachnoclostridium-mediated fermentation of SCFAs, which may serve as foundation for the development of dietary strategies.